Purification and Immunostaining of Mouse Ependymal Ciliary Shafts - Kai Hao; Xueliang Zhu; Xiumin Yan (Bio-Protocol, 2022)
Cilia and flagella are microtubule-based hair-like organelles protruding from the surface of most eukaryotic cells, and play essential roles in cell locomotion, left-right asymmetry, embryo development, and tissue homeostasis. With isolated cilia and flagella, great progress has been made in understanding the composition, structure, and function of cilia. However, the current cilia/flagella isolation methods are deficient in the integrity or productivity of purified cilia when applied to mammalian motile cilia. Here, we describe a new protocol that isolates cilia shafts from mouse ependymal cells, by horizontal shear force and mild detergent. This method enables the production of virtually integral cilia with high yields and less cell body contamination. It is suitable for immunostaining, puromycin labeling assay, and proximity ligation assay of mammalian motile cilia.Graphical abstract: